Effects of irradiation on the mechanical, electrical, and flammability properties of (low‐density polyethylene)/(ethylene‐[vinyl acetate] copolymer) blends containing alumina trihydrate. Issue 2 (8th April 2014) - Bee, Soo‐Tueen; Hassan, Azman; Ratnam, Chantara; Tee, Tiam‐Ting; Sin, Lee Tin
<x xml:space="preserve">Abstract</x> Alumina trihydrate (ATH) was added to (low‐density polyethylene)/(ethylene‐[vinyl acetate] copolymer) blends (LPEs) to enhance their flame resistance. The addition of substantial amounts of ATH has been known to have deleterious effects on the mechanical properties of such blends. Hence, electron beam irradiation was used to improve the mechanical properties of our ATH‐filled LPE specimens. The specimens were irradiated at 50 to 150 kGy before being cut into specified shapes for analysis. The increase in the irradiation dosage increased the gel content as a result of the formation of crosslinked networks. Also, the flame resistance of the LPE blends was enhanced by increasing both the loading level of ATH and the irradiation dosage. However, a high ATH loading level reduced tensile strength and elongation at break. Nevertheless, the electron beam irradiation maintained the tensile strength and elongation of the ATH‐filled blends. In addition, a higher content of ATH in the LPE blends showed reactive interaction with irradiation effects. A higher amount of ATH reduced the electrical resistivity of the blends, but analysis of their surface and volume resistivity showed that the electrical resistance of the ATH‐filled LPE blends could be improved by electron beam irradiation in the range of 50 to 150 kGy. J. VINYL ADDIT. TECHNOL., 20:91–98, 2014. © 2014 Society of Plastics Engineers